Experimental Study of Lubricant Oil Film Behavior on Al6061 under MQL Milling Process - Nur Elya Haniza, Zamiruddin; Nurrina, Rosli; Amiril Sahab, Abdul Sani (2021)
Minumum Quantity Lubrication (MQL) technology has proven to give better surface roughness and tool life performance compared to conventional lubricating method despite its very little usage of lubricant oil.